Little women - Alcott, Louisa May (Iltalie ELi- Teen Readers, 2015)
Joe, Meg, Amy and Beth are the four March sisters, all very different, but always there for each other. With their father away in the American civil war, they all have to work hard to hep their mother.But there's time for fun and games too with their friend, Laurie. Plays, a personal post-office, secret societies and even a bit romance all help to fill their days while they grow up, hoping always for their father's return.
Activities, Glossary.
Contents, Characters.
Keywords: Story; Intermediate level; Language Learning